PENGARUH DOSIS PUPUK KOMPOS ENCENG GONDOK DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica Juncea L.)â€ - Purnama, Rizki Haqa; Santosa, Sartono Joko; Hardiatmi, JM Sri (Innofarm:Jurnal Inovasi Pertanian, 2013)
The research about "The Effect of Dosage Fertilizer Compost Water Hyacinth and Plant Distance on Growth and Yield mustard (Brassica juncea L.)" was done from February 26th to May 16th, 2013 in the village of Kunden, Wirogunan sub district, Kartasura district, Sukoharjo regency. This research aims to study the best dosage and plant distance can improve the growth and yield of mustard plants optimum and the interaction between dosage and plant distance. The research using Randomized Complete Block design (RCBD) consists of two factors treatments with three replications. The research show that: (1) the treatment of dosage fertilizer compost of water hyacinth was effect on improve number of leaves, fresh weight of plant, weight the plant of consumed, and dry weight of plant,(2) the giving fertilizer compost of water hyacinth with dosage 2 kg/m2 is the best dosage because improve growth yield mustard plants optimal namely 11,44 sheet, fresh weight of plant namely 91,16 g, weight the plant of consumed namely 65,24 g , and dry weight of plant namely 7,01 g,(3) the treatment of plant distance was effect on improve number of leaves, length of leaves, fresh weight of plant, weight the plant of consumed, dry weight of plant,and index of harvest , (4) treatment plant distance of 20x20 cm is the best plant distance because improve growth yield mustard plants optimal namely 11 sheet, length of leaves namely 17,94 cm, fresh weight of plant namely 89,46 g, weight the plant of consumed namely 64,62 g, and dry weight of plant namely 7,61 g, (5) no interaction between dosage fertilizer compost water hyacinth and plant distance on growth and yield of mustard. Key words : Compost Water Hyacinth, Plant Distance , mustard